Design and fabricate a movable multifunction table - Mohamad Ilme, Ahmad Bahri (2010)
This report presents the table that more focusing on the computer table and has many functions. It also can use in the lab and movable. Most of the table in the laboratory is fixed and don’t have many function. This table is ease the worker or student in the lab while used it. This report will also show the function of the each part of table. Material used to produce this table is zinc plate. The purpose of the table is designed more focusing on computer table. Ways and forms an attractive installation design to make it easy to used. Several aspects should be given full attention to ensure that this project can be carried out in line with the initial planning and be completed within the time supposed.